Tinjauan Buku: Allah Mengizinkan Manusia Mengalami Diri-Nya, Pengalaman dengan Allah dalam Konteks yang Berpancasila - Arthur Aritonang (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2021)
This book is a compilation of writings from Andreas A. Yewangoe, especially in 2017 which was delivered by Yewangoe on various occasions. Yewangoe covers these themes under a big umbrella: “God Permits Humans to Experience Himself. In the first part Yewangoe discusses about dogmatics. Meanwhile, in the second part, Yewangoe discusses religion and society. For readers, this book is an important book to read for both theology students and church members. Yewangoe in this book wants to invite every reader to understand the biblical principles regarding the role of church members in the political arena, the importance of peace efforts among religious adherents in Indonesia, the importance of literacy education in order to raise awareness to be wiser and more responsible in using social media so as to avoid influence. ideologies that are opposite to Pancasila, calls for anarchist demonstrations, or access to information that will arouse terrorist cells in Indonesia, the importance of reading and reflecting on Indonesian history so that we appreciate the struggles of our predecessors even more. And finally, the importance of maintaining Pancasila as the basis of the state as a common home for a pluralistic Indonesia.